The issue of depopulation in selected Southeast European countries through an analytical prism of the human safety concept - Djordjevic, Ivica; Džigurski, Ozren; Dželetović, Milenko (Sociološki pregled, 2023)
Of the ten selected countries in Southeast Europe, seven recorded a demographic deficit during the period 2006-2019. The timeframe of this research is conditional upon the availability of data and the fact that due to the Covid-19 pandemic, data relative to the post-2019 period are not relevant. Using the human security concept as an analytical framework, with the help of statistical analysis based on selected indicators, we have reached the result that the health situation to a highest degree contributed to Slovenia, Montenegro and North Macedonia maintaining approximately the same number of inhabitants, while Albania, Bosnia and Herzegovina, Bulgaria, Serbia, Hungary, Croatia, and Romania recorded a demographic deficit. Research shows that the long-term development strategies of countries should be based on the quality of life of citizens in order to ensure their sustainability and survival.